(untitled) (Research, Society and Development, 2021)
The components that are currently being employed in industrial processes have been subjected to excessive wear due to: their increased usage, the low quality of these products and / or the maintenance and operation services that are provided them, the lack of expertise of the labor employed in the production processes, the decrease in reserves having minerals that are free of contaminants, and the mechanical properties of the metals that are contained in these components. In light of the above, it is clear that, within industrial sectors, substantial losses exist, be they in terms of cost, productivity, safety or even those losses that arise from the work having to be redone or from the dissatisfaction among the personnel due to the substandard performance of the machines and equipment that they must use. The application of materials engineering, through various studies, has developed techniques for the use of polymers in order to increase the service life of these components, resulting in the emergence of subassemblies and / or machines and equipment that are fundamental to this paradigm shift. The ever-present need to reduce costs in the industrial market, whether it be from replacement, breakdowns, refurbishment and accidents due to the premature wear of components, has become a feasible option for many organizations, and, in sum, summarizes the social relevance of this research. Thusly, the following question is being put forth as a research hypothesis: How can Materials Engineering that is focused on increasing the service life of industrial components be applied?